Italian Grape Ale Beers Obtained with Malvasia di Candia Aromatica Grape Variety: Evolution of Phenolic Compounds during Fermentation - Giulia Leni; Elia Romanini; Terenzio Bertuzzi; Alessio Abate; Letizia Bresciani; Milena Lambri; Margherita Dall’Asta; Mario Gabrielli (Foods, 2023)
Italian grape ale (IGA) beers have been categorized by the Beer Judge Certification Program as a sub-category of fruit beers in which grape, or grape must, is added during the brewing process to provide additional characteristics to the final beer. In the present work, IGA beers have been produced with must and pomace of the Malvasia di Candia Aromatica (MaCA) grape variety, which were added before fermentation at two different percentages (10% and 20%). The (poly)phenolic profile of IGA beers have been characterized with HPLC-MS/MS and compared to a golden ale control beer (produced in the same conditions without the addition of grape-derived ingredients). A series of sub-samples have been collected to monitor the (poly)phenol profile at time 0 and during the different phases of the fermentation process (1, 3, 5, 7 30, 65 days). Results demonstrated how the addition of pomace allowed to significantly enrich (p < 0.05) final beers in total (poly)phenols detected by MS, while must addition did not influence that amount if compared to the control sample. However, a PCA cluster analysis identified strong similarities among IGA beers and differentiated them to control beer samples. This study underlined how the addition of must and pomace from the MaCA grape variety improved the (poly)phenolic profile of beer from both a qualitative and quantitative point of view.